Special Education in First Nations Schools in Canada: Policies of Cost Containment - Phillips, Ron (Alberta Journal of Educational Research, 2010)
The education of First Nations students in Canada on reserve is the legal responsibility of the federal government. This article reviews and critiques the federal government’s past and current special education policies and practices in regard to First Nations schools throughout Canada. The author has found that rather than establishing a comprehensive special education system for First Nations schools, the federal government has focused on limiting funding, services, and development. Four themes emerge from this review: (a) lack of willingness on the part of the federal government to honor constitutional obligations and responsibilities in special education to First Nations; (b) focus of providing provincial level of special education services resulted in little consultation with First Nations; (c) limited funding, and (d) lack of respect for First Nations expertise.